Thirst sensation and oral dryness following alcohol intake - Kiyotoshi Inenaga; Kentaro Ono; Suzuro Hitomi; Ayu Kuroki; Izumi Ujihara (Elsevier, 2017)
Substantial acute and chronic intakes of alcohol or ethanol (EtOH) severely influence oral sensations, such as thirst and oral dryness (dry mouth, xerostomia). Thirst sensation and oral dryness are primarily caused by the activation of neurons in brain regions, including the circumventricular organs and hypothalamus, which are referred to as the dipsogenic center, and by a decrease in salivary secretion, respectively. The sensation of thirst experienced after heavy-alcohol drinking is widely regarded as a consequence of EtOH-induced diuresis; however, EtOH in high doses induces anti-diuresis. Recently, it has been proposed that the ethanol metabolite acetaldehyde induces thirst via two distinct processes in the central nervous system from EtOH-induced diuresis, based on the results of animal experiments. The present review describes new insights regarding the induction mechanism of thirst sensation and oral dryness after drinking alcohol.